Five-Year Survival and Associated Factors in Patients with Head and Neck Cancer in the Brazilian Amazon - Lorena Cristine Soares Epaminondas; Maikon da Silva e Silva; Myara Cristiny Monteiro Cardoso; Leonardo Breno do Nascimento de Aviz; Maria Conceição Nascimento Pinheiro; Vânia Cristina Campelo Barroso Carneiro; Laura Maria Tomazi Neves; Saul Rassy Carneiro (Revista Brasileira de Cancerologia)
Introduction: Head and neck cancer accounts for approximately 660,000 new cases annually worldwide and is increasing due to the consequences of interactions among environmental, socioeconomic and genetic factors, making it a multifactorial dysfunction. Objective: To verify the five-year survival and associated factors in patients diagnosed with head and neck cancer in a reference cancer hospital in the Amazon. Method: Hospital-based retrospective cohort study with analysis of 510 medical records of patients admitted and followed up at the hospital from 2009 to 2014, the data were collected between August and November of 2020. The Kaplan-Meier method and the log-rank test were utilized for the statistical analysis, in addition to the Cox regression model to verify the influence of variables on survival time, considering a significance of 0.05. Results: The overall survival rate was 74.7%, socio-demographic variables as women and living in state’s inner cities were associated with the highest survival rates (84.4% and 79.4%, respectively). The clinical variables advanced staging, indication for physiotherapy and smoking were associated with the lowest survival rates with 49.1%, 16.6% and 66.5%, respectively. Conclusion: Sociodemographic and clinical factors are involved in the survival of patients undergoing treatment for head and neck cancer; in addition, early diagnosis and smoking cessation could potentially increase the survival of these patients.